2021
DOI: 10.3390/cells10092335
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells to Model Juvenile Myelomonocytic Leukemia: New Perspectives for Preclinical Research

Abstract: Juvenile myelomonocytic leukemia (JMML) is a malignant myeloproliferative disorder arising in infants and young children. The origin of this neoplasm is attributed to an early deregulation of the Ras signaling pathway in multipotent hematopoietic stem/progenitor cells. Since JMML is notoriously refractory to conventional cytostatic therapy, allogeneic hematopoietic stem cell transplantation remains the mainstay of curative therapy for most cases. However, alternative therapeutic approaches with small epigeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 149 publications
(253 reference statements)
0
3
0
Order By: Relevance
“…JMML research has been traditionally hindered due to its low incidence (1.2 cases per million children under 14 years of age), and the impossibility of maintaining primary JMML cells in vitro for extended periods of time or establishing immortalized JMML cells lines [ 123 , 124 ]. In this context, the development of methods to generate JMML patient-derived xenografts (PDX) and iPSCs has been instrumental to overcome low sample number difficulties and provide an unlimited source of JMML cells for experimental purposes.…”
Section: Current Challenges and Future Perspectives In Jmml Researchmentioning
confidence: 99%
“…JMML research has been traditionally hindered due to its low incidence (1.2 cases per million children under 14 years of age), and the impossibility of maintaining primary JMML cells in vitro for extended periods of time or establishing immortalized JMML cells lines [ 123 , 124 ]. In this context, the development of methods to generate JMML patient-derived xenografts (PDX) and iPSCs has been instrumental to overcome low sample number difficulties and provide an unlimited source of JMML cells for experimental purposes.…”
Section: Current Challenges and Future Perspectives In Jmml Researchmentioning
confidence: 99%
“…Hypersensitivity of JMML progenitors to GM-CSF, IL3 and TNFa in vitro, hyperproliferation of monocytic and/or granulocytic lineages in vivo, thrombocytopenia, and increased fetal hemoglobin (HbF in 50–60% of patients) are common JMML features, with occasional transformation to ALL, suggesting a disease of, or expressed in, multipotent HSC/MPP [ 204 , 205 , 224 , 225 , 226 , 227 , 228 , 229 ]. A number of recent studies have investigated the cellular origin and clonal evolution of JMML using iPS cell [ 230 , 231 , 232 , 233 , 234 , 235 , 236 ] and xenograft models [ 237 , 238 , 239 ]. Caye et al [ 238 ] demonstrated the propagation of transplanted primary bone marrow JMML HSPCs (particularly those in the PTPN11, NRAS and KRAS subgroups and with a median age of 2.2 years) in immunodeficient NSG and NSG-SGM3 mice.…”
Section: Pediatric Aml and Juvenile Myelomonocytic Leukemia (Jmml)mentioning
confidence: 99%
“…In fact, maintaining immature JMML progenitor cells in culture poses a big challenge, as they tend to differentiate and undergo rapid senescence. Indeed, it is possible to maintain undifferentiated JMML cells for approximately 2 weeks in medium supplemented with different types of cytokines [13]. Moreover, AML primary blasts are difficult to maintain in culture as well, due to rapid differentiation and undergoing apoptosis in ex vivo cultures, and they often need the bone marrow support or addition of small molecules such as Aryl hydrocarbon suppressor [14].…”
Section: Introductionmentioning
confidence: 99%